Improved Detection of Breast Cancer Nuclei using Modular Neural Networks - Schnorrenberg, Frank; Tsapatsoulis, Nicolas; Pattichis, Constantinos S.; Schizas, Christos N.; Kollias, Stefanos D.; Vassiliou, Mary; Adamou, Adamos; Kyriacou, Kyriacos C. (My University, 2000)
Discusses the analysis of nuclei in histopathological sections with a system that closely simulates human experts. The evaluation of immunocytochemically stained histopathological sections presents a complex problem due to many variations that are inherent in the methodology. In this respect, many aspects of immunocytochemistry remain unresolved, despite the fact that results may carry important diagnostic, prognostic, and therapeutic information. In this article, a modular neural network-based approach to the detection and classification of breast cancer nuclei stained for steroid receptors in histopathological sections is described and evaluated.
Keywords: Biomedical; Breast cancer Nuclei; Modular Neural Network